The Effect of Curcumin Powder and Cloves Oil on the Properties of Fibers Produced by Electrospinning Technology (Baghdad Science Journal, 2024)
Electrospinning is a simple method for obtaining nanofibers. They possess distinctive ‎properties such as large surface area to weight and high porosity, which make them attractive for many ‎applications. In this research, the electrospinning technique was used to obtain non-woven mats of ‎fibers using polylactic acid (PLA) with the addition of curcumin powder and clove oil as natural ‎antibacterial materials. For the preparation of mats, a 10% polylactic acid solution was prepared in ‎a mixture of acetone and dimethylformamide. Natural materials were added to the ‎polymer solution in several concentrations of 1, 3, 5, 7, and 10%. The viscosity of these solutions was ‎measured. The samples were then prepared using a locally manufactured ‎electro-spinner. Using a scanning electron microscope, it was ‎found that the average diameter of the fibers of the polylactic acid sample is 177 nm. It is noted ‎that the diameters of the fibers produced using polymer and natural materials have larger ‎diameters, especially when curcumin is added, as the fiber diameters range between 485 and 764 nm. ‎The activity of the produced samples against two types of Gram-negative and Gram-positive bacteria ‎was tested. It was found that the polymer-only sample did not have any resistance to the bacteria. ‎While samples containing natural materials showed antibacterial activity against both types of bacteria.‎ It was noted that this activity increased with the increase in the concentration of the additive, which ‎produced ‎an increase in the diameter of the inhibition zone, which makes it suitable for medical and ‎other ‎applications.‎